Phosphate-solubilizing bacteria from upland rice (Oryza sativa L.) rhizosphere and their tricalcium phosphate solubilizing abilities - Cavite, H. J.M.; Mactal, A. G.M.; Cruz, J. A.; Khermkhan, J. (My University, 2018)
Insoluble forms of phosphorus (P) may be converted to soluble P by phosphate-solubilizing organisms living different soil ecosystems to make them available for plant roots to be absorbed. In this study, isolation of rhizobacteria and screening of their ability for phosphate solubilization was done. A total of 25 isolates were obtained from upland rice rhizosphere in Isabela province, Philippines. Measuring the solubilizing efficiency revealed that seven out of 25 isolates were found to be promising phosphate-solubilizers showing clearing zone around the colony. Moreover, phosphorus solubilization index (PSI) of the isolates ranged from 1.25 to 1.60 and results obtained are higher than other observations indicating that strains of bacteria isolated are effective phosphate-solubilizers. Furthermore, these PSB could serve as efficient biofertilizer candidates for improving the P nutrition of the crop. This observation can be a promising contribution to cropping system of upland rice, which is constrained by drought leading to inefficient P acquisition. If further developed, this can be eco-friendly and prove to be cost effective strategy to improve upland rice production particularly in the Philippines.
Keywords: Isolation; Phosphate-solubilizing bacteria; Rhizobacteria; Screening; Solubilization index; Upland rice